Lattice Boltzmann modelling of droplets on chemically heterogeneous surfaces - Dupuis, A; Yeomans, J (2004)
We use a three-dimensional lattice Boltzmann model to investigate the spreading of mesoscopic droplets on homogeneous and heterogeneous surfaces. On a homogeneous substrate the base radius of the droplet grows with time as t(0.28) for a range of viscosities and surface tensions. The time evolutions collapse onto a single curve as a function of a dimensionless time. On a surface comprising of alternate lyophobic and lyophilic stripes the wetting velocity is anisotropic and the equilibrium shape of the droplet reflects the wetting properties of the underlying substrate. (C) 2003 Elsevier B.V. All rights reserved.